Linking cancer registry and hospital discharge data for treatment surveillance. (June 2013) - Lin, Ge; Ma, Jihyun; Zhang, Lei; Qu, Ming
Cancer registry data often lack complete chemotherapy and radiation therapy information. To conduct treatment disparity surveillance, we linked 2005–2009 Nebraska Cancer Registry data with Nebraska hospital discharge data. Due to the high quality of both datasets and the proposed linkage procedure, we had a linkage rate of 97 percent. We demonstrate the utilization of the linked dataset in case finding, treatment update, and treatment surveillance. The results show that the linked dataset is likely to identify up to 5 percent of potential missed cases. We investigated the use of radiation therapy in treating colorectal and breast cancers as case-finding examples. The linked dataset found 12 percent and 14 percent more treatment cases for colorectal and breast cancer patients, respectively.